2014
DOI: 10.1063/1.4897953
|View full text |Cite
|
Sign up to set email alerts
|

Reversed boiling curve phenomenon on surfaces with interlaced wettability

Abstract: We experimentally investigated the effects of contact angle difference of heterogeneous wettability surfaces on pool boiling. For surfaces exhibiting heterogeneous wettability, this study determined that the pool boiling curve experiences a superheat decrease in some regions before the system achieves the critical heat flux. In addition, oscillation of the vapor column and bubble transverse motions on the heterogeneous wettability coated surface were observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(2 citation statements)
references
References 15 publications
1
1
0
Order By: Relevance
“…4) indicate that the tested surfaces exhibited similar boiling performance in both saturated and subcooled conditions. The lowest heat transfer coefficient was measured on the bare (untreated) stainless steel sample, where part of the boiling curve has a negative slope (at heat fluxes higher than 125 kW/m 2 ), as experimentally observed in previous studies [30]. During the saturated experiment [ Fig.…”
Section: Boiling Performancesupporting
confidence: 63%
“…4) indicate that the tested surfaces exhibited similar boiling performance in both saturated and subcooled conditions. The lowest heat transfer coefficient was measured on the bare (untreated) stainless steel sample, where part of the boiling curve has a negative slope (at heat fluxes higher than 125 kW/m 2 ), as experimentally observed in previous studies [30]. During the saturated experiment [ Fig.…”
Section: Boiling Performancesupporting
confidence: 63%
“…These results might explain the mixed wettability occur higher heat transfer coefficient at temperature region of nucleate boiling as reported by previous studies. [44][45][46] In the case of mixed wettability at 110 C of initial surface temperature, it should be noted that surface temperature decreased to 104 C upon the contact between droplet and surface. However, the boiling curve indicated that this temperature region is natural convection boiling.…”
mentioning
confidence: 99%